Renal manifestations of systemic autoimmune disease: diagnosis and therapy. - O'Callaghan, C (2004)
Renal involvement is relatively common in certain systemic autoimmune diseases, but can be clinically silent. Active surveillance is, therefore, essential because the early recognition of renal involvement may influence the extent of renal recovery. Blood pressure control is also essential, regardless of the underlying disease. In systemic lupus erythematosus, therapy usually depends on the renal biopsy findings as not all forms of renal involvement respond in the same way. Typically, for aggressive disease, therapy is with steroids and a cytotoxic agent, usually cyclophosphamide initially and then azathioprine. In systemic vasculitis with renal involvement, a similar approach is adopted, therapy including steroids and cyclophosphamide initially and then steroids and azathioprine. With severe fulminant disease, plasma exchange or pulsed intravenous methylprednisolone is added initially. Scleroderma renal crises are managed by blood pressure control using angiotensin-converting enzyme inhibitors and other agents as required. Dialysis and transplantation can be successful in these conditions.